Right to health services for people with HIV/AIDS in Bandarlampung: Challenges and fulfillment - Salma Diva Aurora; HS Tisnanta; Agus Triono (Annals of Justice and Humanity, 2023)
Purpose: This study aimed to determine how the right to health services is fulfilled for people living with HIV/AIDS (PLWHA) in Bandar Lampung City and what are the obstacles to fulfilling the right to health services for HIV/AIDS sufferers there. Research Methodology: This research uses empirical normative research that employs a literature study approach and research directly at the research location. The data sources for this research were the library and field data. Results: The research results show that: (1) Fulfillment of the right to health services for people with HIV/AIDS in Bandar Lampung City has been implemented in accordance with Minister of Health Regulation (PMK) Number 23 of 2022 concerning the Management of HIV AIDS and Sexually Transmitted Infections. Fulfillment is realized by the availability of health services for HIV/AIDS sufferers in hospitals, community health centers, and organizations that focus on HIV/AIDS issues and have special programs for HIV/AIDS sufferers. Limitations: In reality, there are still obstacles faced in fulfilling the right to health services for people with HIV/AIDS in Bandar Lampung City, namely inadequate financial support, antiretroviral drugs that are still dependent on the center, as well as stigma and discrimination by health workers towards HIV/AIDS sufferers. Contribution: Human Immunodeficiency Virus (HIV) / Acquired Immune Deficiency Syndrome (AIDS) has been declared a world pandemic and a disease that is a serious health problem. HIV/AIDS sufferers sometimes experience difficulties in getting health services.